Zoneamento (geo)ambiental analítico da bacia hidrográfica do Rio do Monjolinho São Carlos (SP) - Campanelli, Leandro Contri (Universidade Federal de São Carlos, 2012)
Today s administrators are increasingly adopting a river basin as a planning and management unit. A river basin consists of a physical and biogeophysiographic unit with delimited boundaries, which can extend to several spatial scales. Environmental zoning a much-used tool in environmental planning of watersheds may be defined as the compartmentalization of a given area into zones according to its most relevant attributes and dynamics. Along these lines, this study aimed to obtain an analytical (geo)environmental zoning chart of Monjolinho river basin (São Carlos, SP, Brazil) at 1:50,000 scale with the purpose of assisting planners and administrators in managing urban occupation, thereby minimizing impacts to the environment. Monjolinho river basin encompasses an area of 275km2, most of which located in the municipality of São Carlos (a smaller part of which located in the neighboring municipality of Ibaté). The 1:50,000-scale cartographic documents generated including maps and charts representing different components of the physical environment that assisted in the analytical (geo)environmental zoning of the watershed in question were: registration map, declivity chart, map of land use and coverage, map of surface geological formations, map of unconsolidated materials, map of aquifer units, and map of primary compartmentalization units. The resulting product of this study was an analytical (geo)environmental zoning chart of Monjolinho river basin, centered on the process of urban occupation. This cartographic document compartmentalizes this basin into the following classes of appropriateness to urban occupation: suitable areas, unfavorable areas, and unsuitable areas.
Keywords: Planejamento físico-ambiental; Bacia Hidrográfica; Zoneamento (Geo)ambiental Analítico; Watershed; Analytical (Geo)environmental Zoning; ENGENHARIAS